A General Control Algorithm for Cooling Towers in Cooling Plants with Electric and/or Gas-Driven Chillers - Braun, James E. (HVAC&R research, 2007)
A hybrid chiller plant employs a combination of chillers that are "powered" by electricity and natural gas. This paper presents an algorithm for determining cooling tower fan settings in hybrid plants in response to loadings on individual chillers. Parameters of the algorithm are evaluated using design information for the chillers and cooling tower fans. In addition to reducing operating costs, use of the open-loop control strategy simplifies the control and improves the stability of the tower control compared with the use of a constant condenser water supply or approach to wet-bulb. Simulated plant cooling costs associated with the algorithm were compared with costs for optimized settings and were within 1% of the minimum costs. The control method is general, in the sense that it also applies to cooling plants that have all electric or all natural gas chillers.